Safeguarding children from emotional maltreatment : what works - Barlow, Jane, 1962- (Safeguarding children across services series., 2010)
Emotional maltreatment is widespread and has a profoundly harmful effect on a child's development. The effects of abuse are often carried into adulthood, and emotionally abused children are more likely to experience a range of problems as adults including depression, substance misuse and eating disorders. This book sets out to identify 'what works' in preventing emotional maltreatment from recurring. Since most emotional maltreatment takes place within the family home, involves the primary care-giver and reflects ongoing patterns of damaging parent-child interaction rather than isolated incide.